2017
DOI: 10.1542/peds.2016-2863
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Serial Strategies for Preventing Wrong-Patient Orders in the NICU

Abstract: The risk of wrong-patient orders in the NICU was significantly higher than in non-NICU pediatric units. Implementation of a combined ID reentry intervention and distinct naming convention greatly reduced this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 6 publications
1
37
0
6
Order By: Relevance
“…16,18 However, several publications related to reports in pediatrics have mostly approached medication errors and their potential consequences. [6][7][8][9][10][11][12]14,[27][28][29][30] Still, in Latin American countries, reporting studies are very scarce compared to developed countries. So much that, to our knowledge, this is the first Argentine study that focused exclusively on reports of medication errors in hospitalized children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,18 However, several publications related to reports in pediatrics have mostly approached medication errors and their potential consequences. [6][7][8][9][10][11][12]14,[27][28][29][30] Still, in Latin American countries, reporting studies are very scarce compared to developed countries. So much that, to our knowledge, this is the first Argentine study that focused exclusively on reports of medication errors in hospitalized children.…”
Section: Discussionmentioning
confidence: 99%
“…Voluntary reporting is only one of the multiple pieces that are required at hospitals to reduce and detect errors and AEs in order to improve patient safety. 21,[23][24][25][30][31][32] As observed in this study, medication errors are most commonly reported in a voluntary manner. Most likely, these errors are more easily detected in hospitalized children, by both health care providers and patients' parents, who are usually the first ones to notice them.…”
Section: Discussionmentioning
confidence: 99%
“…RAR has been successfully used to measure the rate of intercepted wrong-patient errors in various settings including emergency departments, 13,14 a children's hospital, 12 and the NICU setting. 4,5…”
Section: Outcomementioning
confidence: 99%
“…However, previous research has shown the viability of using RAR as a proxy for wrong-patient errors in pediatric and neonatal settings. 4,5 For the analysis, we did not have data on clinician-type breakdowns of wrong-patent errors. We only used the standard 10-minute interval from the RAR events; errors that were identified by other clinicians or those that were caught later in the medication workflow were not included in the analysis.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation